2018
DOI: 10.28945/4085
|View full text |Cite
|
Sign up to set email alerts
|

Performance Expectancy, Effort Expectancy, and Facilitating Conditions as Factors Influencing Smart Phones Use for Mobile Learning by Postgraduate Students of the University of Ibadan, Nigeria

Abstract: Aim/Purpose: This study examines the influence of Performance Expectancy (PE), Effort Expectancy (EE), and Facilitating Conditions (FC) on the use of smart phones for mobile learning by postgraduate students in University of Ibadan, Nigeria. Background: Due to the low level of mobile learning adoption by students in Nigeria, three base constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT) model were used as factors to determine smart phone use for mobile learning by the postgraduate stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 9 publications
9
49
1
Order By: Relevance
“…Therefore, the third hypothesis is: H3: Performance expectancy has significant effect to behavior intention. Effort expectancy is defined as user perception of how they can use a technology easily (Onaolapo & Oyewole, 2018). The effect of effort expectancy on behavior intention is found as significant in previous empirical evidences.…”
Section: Research Model and Hypothesismentioning
confidence: 92%
“…Therefore, the third hypothesis is: H3: Performance expectancy has significant effect to behavior intention. Effort expectancy is defined as user perception of how they can use a technology easily (Onaolapo & Oyewole, 2018). The effect of effort expectancy on behavior intention is found as significant in previous empirical evidences.…”
Section: Research Model and Hypothesismentioning
confidence: 92%
“…The study of (Ghalandari, 2012) on mobile banking service stated users' intention to use technology becomes positive when they found a particular system requires less effort to use or operate. (Onaolapo & Oyewole, 2018) found that effort expectancy towards the use of smartphones for mobile learning showed a significant positive relationship. Moreover, other findings also suggest direct influences of effort expectancy on users' intention to adopt a technology (Alalwan, Dwivedi, & Williams, 2014; M. Z.…”
Section: Effort Expectancy (Ee) and Intention To Usementioning
confidence: 94%
“…Several studies have suggested PE as one of the primary factors that predict the use of IT 1,[27][28][29][30][31][32] and even the strongest predictor of the use of IT. 15,33 For example, Pai and Huang 34 indicated that PE affects intention to use HIS. Carlsson 35 revealed that PE is associated with intention to use mobile devices.…”
Section: Utaut Modelmentioning
confidence: 99%